Macro-Level Activity Spaces: A Reply. - White, Stephen E. (Professional Geographer)
This article presents author's clarification in response to A. Stewart Fotheringham's comments about his article on macro-level activity space research. The author denies Fotheringham's comments on the gravity model used by him to draw conclusions about visitation patterns between U.S. cities. He claims that the distance-decay curves that are depicted in his article are valuable for drawing conclusions for two reasons. First, the slopes of the curves are unbiased and can be compared, as claimed. Second, the author clarifies that the variance in the degree to which the constants were underestimated is likely to be small because the range of R values for the six equations is not very large and, as Fotheringham noted, the underestimation decreases as the R value approaches one.